Is Separation of Powers a Useless Concept? Part II: Tripartite System Criticism and Application Problems - Hapla, Martin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
In this paper, the author raised the question of whether the separation of powers is a useless concept. It summarizes some critical arguments against the tripartite separation of powers. The paper deals with application issues related to the separation of powers and distinguishes several attitudes toward them, which it then analyses in more detail. Great attention is dedicated to formalism and functionalism. Eventually, the author wonders whether it would be better to innovate the idea of separation of powers, or to dismiss and replace it with some other principle. He concludes that the separation of powers has problems, but we need to evaluate this idea in relation to its possible alternatives. In such a light it still sounds promising.